2019
DOI: 10.33564/ijeast.2019.v04i05.006
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Hospital Waste Management of Sylhet City in Bangladesh

Abstract: Infectious and hazardous medical waste poses a deliberate threat to environmental health and needs special treatment and management prior to its ultimate disposal. Many of hospitals in Sylhet have neither a satisfactory waste management system nor a disposal policy. This study represents the present status of Hospital Waste (HW) management in Sylhet city, Bangladesh. A survey has been conducted using a questionnaire to collect information about the practices related to waste segregation, collection procedures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Although the OPD generates the biggest amount of CSW, most of the wastes in this department are non-hazardous. This result is similar with some studies who found out that 64% of CSW in hospitals are generated in the OPD and are non-hazardous [19,20].…”
Section: Department That Generates the Biggest Amount Of Csw At Jthsupporting
confidence: 92%
“…Although the OPD generates the biggest amount of CSW, most of the wastes in this department are non-hazardous. This result is similar with some studies who found out that 64% of CSW in hospitals are generated in the OPD and are non-hazardous [19,20].…”
Section: Department That Generates the Biggest Amount Of Csw At Jthsupporting
confidence: 92%
“…This waste is basically composed of hazardous and nonhazardous items. On the basis of the risk associated with these waste products during their handling and processing they are further categorized into (a) sharps including contaminated needles and scalpels, (b) pathological waste items including microbiological cultures, blood samples, and body parts, (c) infectious waste materials including blood and body fluids specimens, intravenous lines and catheters and dressings [21][22][23] . Aside from these materials other waste items include instruments containing radioactive agents and mercury, and polyvinyl chloride (PVC) plastics 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, design of incinerator and its flue gas monitoring is very important for successful adoption of this technique. Basak et al (2019) and Vavva et al (2020) stated that incineration of hospital waste can be a best practice to manage and properly dispose toxic and hazardous hospital wastes. The knowledge of waste generated at the medical and hospital waste facilities is very important for proper handling and safe disposal of hazardous wastes, reported by Ali et al (2020).…”
Section: Introductionmentioning
confidence: 99%